High-speed gas injector for powerful plasmadynamic systems - Staltsov, V.V.; Chebotarev, V.V.; Makhlaj, V.A. (Вопросы атомной науки и техники, 2015)
The paper describes the design features of gas injectors for the axial (parallel to the axis of the accelerator) and radial (perpendicular to the axis of the accelerator) working gas supply into the accelerator channel. The results of gas-dynamic studies of the injectors are presented. The amount of the working gas inlet was investigated as a function of gas pressure under the blocking valve element. A strong dependence of the amount of the injected working gas on the current value in the control coil was found. Описываются особенности конструкции газовых инжекторов для осевой (параллельной оси ускорителя) и радиальной (перпендикулярной оси ускорителя) подачи газа в ускорительный канал. Представлены результаты газодинамических исследований инжекторов. Исследована зависимость количества напускаемого рабочего газа в зависимости от давления газа под запирающим элементом клапана. Показана существенная зависимость количества инжектированного рабочего газа от величины тока в управляющей катушке. Описуються особливості конструкції газових інжекторів для вісьової (паралельної осі прискорювача) і радіальної (перпендикулярної осі прискорювача) подачі газу в прискорювальний канал. Представлені результати газодинамічних досліджень інжекторів. Досліджена залежність кількості робочого газу, що напускається, залежно від тиску газу під замикаючим елементом клапана. Показана істотна залежність кількості робочого газу, що напускається, від величини струму в котушці, що управляє.